Modification of RNF183 via m6A Methylation Mediates Podocyte Dysfunction in Diabetic Nephropathy by Regulating PKM2 Ubiquitination and Degradation - Dongwei Guo; Yingxue Pang; Wenjie Wang; Yueying Feng; Luxuan Wang; Yuanyuan Sun; Jun Hao; Fan Li; Song Zhao (Cells, 2025)
Diabetic kidney disease (DKD) is a prevalent complication associated with diabetes in which podocyte dysfunction significantly contributes to the development and progression of the condition. Ring finger protein 183 (RNF183) is an ER-localized, transmembrane ring finger protein with classical E3 ligase activity. However, whether RNF183 is involved in glomerular podocyte dysfunction, which is the mechanism of action of DKD, is still poorly understood. In this study, we first demonstrated that RNF183 expression in glomerular podocytes of patients with DKD decreased as the disease progressed. Additionally, our transcriptome sequencing analysis of kidney tissues from diabetic mice revealed a significant reduction in RNF183 expression within the kidney cortex. Similarly, the expression of RNF183 was significantly reduced both in the kidneys of diabetic mice and in human podocytes exposed to high glucose conditions. The downregulation of RNF183 resulted in a suppression of autophagic activity, an increase in apoptotic cell death, and reduced expression of cellular markers in HPC cells. We found that RNF183 was modified via N6-methyladenosine (m6A) RNA methylation. Meanwhile, treatment with meclofenamic acid 2 (MA2), an m6A demethylase inhibitor, resulted in the upregulation of RNF183 expression in HPC cells cultured in high glucose conditions. Furthermore, high glucose treatment decreased the transcription and protein levels in both the m6A writer methyltransferaselike3 (METTL3) and the m6A reader insulin-like growth factor 2 mRNA-binding protein 2 (IGF2BP2). IGF2BP2 assisted with METTL3, which is jointly involved in the transcription of RNF183. Furthermore, we confirmed that RNF183 directly ubiquitinates M2 pyruvate kinase (PKM2) through co-immunoprecipitation (Co-IP) and liquid chromatography–mass spectrometry (LC-MS) experiments. The level of PKM2 ubiquitination was increased following RNF183 overexpression, leading to enhanced PKM2 protein degradation and subsequently alleviating high glucose-induced podocyte damage. The results of this study indicated that RNF183 was regulated via m6A methylation modification and that RNF183 expression was reduced in HPC cells treated with high glucose, which resulted in decreased PKM2 ubiquitination levels and subsequently aggravated podocyte injury. The findings suggest that RNF183 may serve as a potential therapeutic target for diabetic kidney injury, offering new insights into its role in the progression of DKD.